Prevalence, characterization and clonal analysis of Escherichia coli O157: non-H7 serotypes that carry eae alleles - Feng, Peter C. H. (2010)
Fil: Feng, Peter C.H. Division of Microbiology, FDA, College Park, MD; Estados Unidos.